2017
DOI: 10.1007/s00345-017-2116-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and prognostic value of variant histology and lymphovascular invasion at transurethral resection of bladder

Abstract: Detection of LVI is missed in a third of TUR specimens while VH seems more accurately identified. TUR LVI and VH are associated with more advanced disease and LVI predicts disease recurrence. Assessment and reporting of LVI and VH on TUR specimen are important for risk stratification and decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Anyway, in our study variant histology at TUR was associated to APF after RC at multivariable logistic regression analyses (p = 0.007). Our results are in accordance with Abufaraj et al [20], who reported a significant relationship (p = 0.04) between variant histology at TUR and APF (such as lymph node metastasis and advanced pathological T stage). All these findings support results reported in several previous studies, which have underlined the importance of variant histology as prognostic factor in patients affected by BCa in term of higher risk of APF, worse survival outcomes [21] and also higher risk of progression in patients with non-muscle invasive bladder disease [22] compared to patients affected by standard urothelial histology.…”
Section: Discussionsupporting
confidence: 93%
“…Anyway, in our study variant histology at TUR was associated to APF after RC at multivariable logistic regression analyses (p = 0.007). Our results are in accordance with Abufaraj et al [20], who reported a significant relationship (p = 0.04) between variant histology at TUR and APF (such as lymph node metastasis and advanced pathological T stage). All these findings support results reported in several previous studies, which have underlined the importance of variant histology as prognostic factor in patients affected by BCa in term of higher risk of APF, worse survival outcomes [21] and also higher risk of progression in patients with non-muscle invasive bladder disease [22] compared to patients affected by standard urothelial histology.…”
Section: Discussionsupporting
confidence: 93%
“…These rates were comparable to those described in the literature. The rate of LVI at TURBT has been reported as 6-70%, and the rate of LVI at RC has been reported to range from 30-50% [1]. Clinical stage and pathological T stage were higher in the LVI-positive group than in the LVI-negative group at rst TURBT.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of lymphovascular invasion (LVI) has been suggested to predict poor prognosis of bladder cancer, such as more advanced disease and recurrence, and has been reported as a poor prognostic factor even for other carcinomas [1][2][3][4][5][6][7][8][9][10]. As transurethral resection of bladder tumor (TURBT) is a standard treatment for bladder cancer, the utility of identifying LVI in specimens of TURBT has been suggested [1][2][3][4][5][6][7][9][10][11][12][13]. The presence of LVI in TURBT specimens has been associated with pathologic upstaging and reduced recurrence-free survival (RFS) and progression-free survival [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors not included in the EORTC or the CUETO models might enhance their usefulness. Hydronephrosis as well as micropapillary or neuroendocrine variant histology could help identify patients who are likely to need multimodal intensified therapy [56]. An additional key feature with which to identify patients with aggressive biology and poor outcomes is LVI.…”
Section: Discussionmentioning
confidence: 99%